Program Pembiayaan Lembaga Keuangan Mikro Syariah (LKMS) dalam Peningkatan Kesejahteraan Pelaku Usaha Mikro (Studi Kasus BMT Baitul Karim Bekasi) - Widya Gina; Jaenal Effendi (Department of Islamic Economics, IPB University, 2015)
The role of micro business enterprises in employment is quite large, namely 99.9% of the total workforce in Indonesia. This suggests that micro businesses have a great opportunity in economic development and increased prosperity. This is not in accordance with the improvement of social welfare of the poor because of the high of the poor up to 10.96% of the total population. The limited capital on micro businesses is an obstacle that is difficult to be avoided. In this case, the financing provided by the BMT is crucial for micro enterprises in accessing capital. The purpose of this study is to analyze the effect of the financing program in increasing income and welfare of micro businesses. The method used in this research is the method of Ordinary Least Square (OLS and logistics method. Significant variables that positively affect the revenue are captured financing of respondents, the number of family members whose income, education, and ethical and moral variables. The variables that positively and significantly affect the welfare are the length of time member, meal expenses, average income, and financing that are taken by respondents.